LABORATORY MONITORING OF PERIODONT INFLAMMATORY DISEASES - Rustamova Sаbogul Mamarejabovna; Xadjimetov Abdugafur Axatovich (Western European Studies, 2024)
It is known that periodontitis is a multifactorial chronic irreversible inflammatory disease that affects the supporting structures of the teeth, initiated and spread by a complex interaction between periopathogens and the host's immune system. It begins with a microbial infection, followed by periodontal tissue damage caused by leukocyte hyperactivity, cytokines, eicosanoids and matrix metalloproteinases. Based on the assessment of their diagnostic properties, the most informative laboratory biomarkers of oral fluid microflora, proteolytic enzymes cathepsin, elastase, haptoglobin, IL-1, IL-4, IL-6, IL-8, IL-10 and TNF-α were determined in gingivitis and chronic periodontitis. It allows to evaluate the diagnostic efficiency of these markers in patients with periodontal diseases and to use them for early diagnosis in non-invasive diagnostics
Keywords: Chronic disseminated periodontitis; gingivitis; oral fluid